TUMOR VENÉREO TRANSMISSÍVEL CANINO EM UMA FÊMEA - Da Silva, Luana Silva; Morais, Laura Eliza; Teichmann, Cristiane Elise; Fraga, Denize Da Rosa; Beck, Cristiane (Salão do Conhecimento, 2018)
Relato de caso supervisionado realizado no curso de Medicina Veterinária da Unijuí